Evaluasi Program Pemberdayaan Dan Pengawasan Melalui Kegiatan Safari Ormas Oleh Badan Kesatuan Bangsa Dan Politik Kota Bandung - Rahma Siti Fadillah; Ely Sufianti; Achmad Sodik Sudrajat; Alikha Novira (Universitas Mbojo Bima, 2025)
Community Organization (Ormas) development is an essential aspect of maintaining social stability and enhancing public participation in development. The Bandung City Government, through the National Unity and Political Agency (Bakesbangpol), organizes the Safari Ormas program as a means of facilitation and education for local community organizations. This study aims to: (1) evaluate the empowerment and supervision program through Safari Ormas by Bakesbangpol Bandung; (2) identify the challenges in implementing the Safari Ormas activities in Bandung; and (3) formulate recommendations to improve the effectiveness of Safari Ormas in supporting empowerment and supervision efforts. This research employed a qualitative approach with data collection techniques including interviews, observations, and documentation. The informants consisted of Bakesbangpol Bandung officials directly involved in Safari Ormas and representatives of several participating organizations. The study applied the CIPP evaluation model developed by Daniel L. Stufflebeam to assess program success. The findings indicate that the implementation of Safari Ormas still faces several challenges, including the low level of organizational understanding among communities, limited budget and human resources (only 2–3 personnel), inconsistent scheduling, and the lack of continuous follow-up after the activity. The recommendations include developing digital training media such as posters, strengthening inter-agency collaboration and utilizing webinars or e-learning, preparing a more structured annual schedule disseminated to Ormas, and reinforcing periodic monitoring and evaluation to ensure the sustainability of program outcomes.